Pandawara Group's Social Campaign "Not Cleaning But Reducing": Sentiment, Responses and Actions of Public On Social Media - setyastuti, yuanita; Maulina, Novaria (KOMUNIKA, 2025)
This research aims to determine the actions carried out by the Pandawara Group and the public's response and sentiment in the context of the social movement carried out by @pandawaragroup on social media. The research method used is a qualitative approach with a descriptive research type. Data collection was carried out through social media searches from March to April 2024. The data analysis technique was discourse analysis of posts related to the Pandawara Group on social media, by Brand24 Application. The research results show that the social movement carried out by the @pandawaragroup account with the tagline "Not cleaning but reducing" has fulfilled the three campaign stages according to Ostegraard (2002): awareness, attitude, and action. This is demonstrated by the participation of social media users in cleaning up rubbish in rivers and beaches. Apart from that, research findings show that the response given by social media users to this social movement is by re-sharing content, providing comments, and uploading using the hashtags #pandawara #pandwaragroup #onedayonetrashbag. The public sentiment that emerged regarding the social movement carried out by the Pandawara Group was divided into positive and negative sentiments. Positive sentiment emerged through mentions and posts expressing support and appreciation for the Pandawara Group's actions, while negative public sentiment regarding the Pandawara Group emerged based on concerns about the lack of government support and low public awareness of protecting the environment.